Second home owners as tourism trend-setters: A case of residential tourists in Gran Canaria - Hannonen, Olga (Journal of Tourism, Sustainability and Well-being, 2018)
This study examines German-speaking second home owners on Gran Canaria, Spain as an example of one of the growing groups of non-conventional tourists. International second home ownership has been increasing rapidly over the last decades with Spain and particularly the Canary Islands being a hot spot for residential tourism. Despite the maturity of the destination, there are few studies on second home tourists on the Canary Islands. Moreover, while second home tourism, including its international forms, has been present as a distinct type of tourism, academic attention has not sufficiently compared and counterposed mass and residential tourism. The aim of this paper is to investigate distinctions between second home and mass tourists to define the features of non-conventional travellers in light of the contemporary growth of alternative ways to engage in recreation. This paper argues that second home tourism reflects the emerging tourism trends of “home stay tourism” and “living like a local” that will reshape the nature of mass tourism as well as receiving destinations. In order to understand the features of rapidly growing alternative or non-mass tourists, this paper examines the experiences of German-speaking second home owners on Gran Canaria. The results reveal a number of distinctive features that collectively help to understand contemporary non-conventional tourists.